2019
DOI: 10.1016/j.devcel.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis Overcomes Directional Bias in Dendritic Cells Due to Hydraulic Resistance and Facilitates Space Exploration

Abstract: Highlights d Macropinocytosis renders migrating cells insensitive to hydraulic resistance (HR) d HR resistance may facilitate space exploration by immature dendritic cells d Mature dendritic cells are not macropinocytic and are thus guided by HR d HR guidance results from a small force imbalance amplified by actomyosin instability

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 62 publications
4
66
0
Order By: Relevance
“…To further investigate this aspect, we added a fluorescent dye FITC Dextran (70kD) into the loading channel at the right-hand side of the chip, together with the chemoattractant. We observed that as the cell protrudes into the blind channels the fluid was displaced around the leading edge, while there was no evidence for micropinocytosis as has been reported for immature dendritic cells recently (32). These results appear to indicate that that cells are only able to migrate into dead-end channels under conditions where they can deform sufficiently to shunt some fluid between the wall and membrane to generate space to move into.…”
Section: Decoupling Chemical Signal From Hydraulic Resistancesupporting
confidence: 66%
See 1 more Smart Citation
“…To further investigate this aspect, we added a fluorescent dye FITC Dextran (70kD) into the loading channel at the right-hand side of the chip, together with the chemoattractant. We observed that as the cell protrudes into the blind channels the fluid was displaced around the leading edge, while there was no evidence for micropinocytosis as has been reported for immature dendritic cells recently (32). These results appear to indicate that that cells are only able to migrate into dead-end channels under conditions where they can deform sufficiently to shunt some fluid between the wall and membrane to generate space to move into.…”
Section: Decoupling Chemical Signal From Hydraulic Resistancesupporting
confidence: 66%
“…This is assumed to create a net influx of water at the leading edge and a net outflow at the uropod driving the cells motion and represents an alternative to the actin-driven motion ('Osmotic Engine Model' (39)). Recent work by Moreau et al (32) suggested that immature dendritic cells (DCs) cells could cope with high hydraulic resistance via a high level of macro-pinocytosis, that allows fluid transport across the cell and thereby exploration of dead-end channels (40). Mature DCs down-regulate macropinocytosis and lose the ability to penetrate dead-end channels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the capacity of migration following hydraulic gradients in the absence of chemical cues is called barotaxis. Several experiments have demonstrated that cells confined to bifurcating channels select the channel of lower hydraulic resistance to orientate and migrate [36,37]. Interestingly, barotaxis does not need chemical attractors, although both barotaxis and chemotaxis may cooperate influencing cell migration, for example in neutrophils [36] and dendritic cells [37], under specific circumstances.…”
Section: External Stimuli Migration and Cancermentioning
confidence: 99%
“…Several experiments have demonstrated that cells confined to bifurcating channels select the channel of lower hydraulic resistance to orientate and migrate [36,37]. Interestingly, barotaxis does not need chemical attractors, although both barotaxis and chemotaxis may cooperate influencing cell migration, for example in neutrophils [36] and dendritic cells [37], under specific circumstances. In a system of competition between chemotaxis with the peptide fMLP against barotaxis, Prentice-Mott et al [36] showed that large cells with high asymmetrical capacities did not respond to chemotactic stimulus and directed their movements to low-resistance channels, whereas neutrophils (small cells with lesser asymmetric potential) could successfully overcome high hydraulic pressures to reach the chemotactic stimulus.…”
Section: External Stimuli Migration and Cancermentioning
confidence: 99%
“…We therefore predict that speed-persistence coupling may not be visible in in vivo imaging data of T cells patrolling the epidermis: in such an environment, both speed and persistence likely reflect the maximum of what is feasible given the environmental constraints rather than being the result of an intrinsic coupling. In complex, highly restrictive environments, cells may choose the path of least resistance (39), with a lesser role for their intrinsic polarity mechanism in this context. But compared to most other tissues, the epidermis is an extreme example of a confining environment.…”
Section: Discussionmentioning
confidence: 99%